Psychosocial support during the COVID-19 pandemic in informal settlements: A Case of Childcare Providers in Nairobi, Kenya - Ivy Chumo; Blessing Mberu; Hellen Gitau; Ivy Nandongwa; Yohannes Dibaba; Caroline Kabaria (SSM - Mental Health, 2023)
Background: The Covid-19 pandemic has placed a significant burden on psychosocial health and wellbeing of childcare providers. The need to support childcare managers has been recognized. However, there is to date little research specifically on how best to support the mental health needs of childcare providers, and no studies on their own experiences and views about what might be most helpful. We set out to address this research gap by qualitatively exploring the psychosocial experiences of childcare providers in Korogocho and Viwandani informal settlements in Nairobi, Kenya. Methods: We collected data through key informant interviews with thirty-two childcare providers who were recruited purposively from Korogocho and Viwandani informal settlements. We analysed the data using framework analysis. Results: We organized the results into six psychosocial support domains derived from themes identified during coding and analysis. As such, experiences and views about psychosocial support were diverse, ranging from self or individual; family and friends; colleagues, peers and teams; organizational; media and the wider public to specialized psychological support services. Colleagues and teams were most childcare centres' first line of support. Notably, like psychosocial support from self, family, organization, media and specialized support services, there were several caveats. Particularly, peer support was described to be a burden to other childcare providers. Conclusions: There is a need to strengthen psychosocial support from colleagues and teams, as it was the most preferred support. Further, there is a need for preparedness and response plans concerning the psychosocial consequences in an outbreak. As such, organisations, governments and other health and wellbeing actors ought to put measures in place to curb not only the physical health of individuals but also their psychosocial wellbeing as well. We recommend that psychosocial support structures of all nature by key actors in organisations should be kept operating during and beyond a crisis. More research is needed to fully unpack the structural, systemic and individual barriers to accessing psychosocial support during and beyond a pandemic.